BARNABAS OR SAUL: WHO IS DESCRIBING SAUL’S CONVERSION IN ACTS 9:27? - Wilson, Mark W. (Scriptura, 2015)
This article examines a problem of translation in Acts 9:27 regarding who should be the subject of the sentence - Barnabas or Saul. Through a close examination of the Greek text in its broader pericope, it explores whether Barnabas was the one who told the apostles in Jerusalem about Saul’s conversion. It also discusses the importance of eyewitness testimony to Luke in his Gospel and Acts. The article closes with a fresh observation about the conversion account’s significance within the narrative structure of Acts.